Are diverse ecosystems more valuable? A conceptual framework for economic valuation of biodiversity - Bartosz Bartkowski (Helmholtz-Zentrum für Umweltforschung (UFZ), 2016)
Biodiversity is an important environmental public good. However, the literature suggests that it is not clear how its economic value should be estimated; there is no established framework for doing this. This paper summarises concepts of biodiversity value from the ecological and economic literatures and combines them to a comprehensive and consistent framework. It is argued that biodiversity is the main carrier of insurance value, option value and spill-over value, and also influences the aesthetic appreciation of ecosystems. On that basis, an extension of the TEV framework is proposed to incorporate biodiversity values better. Furthermore, a number of specific challenges of biodiversity as an economic good are identified and used as criteria to inform the choice of suitable valuation methods.
Keywords: 330; biodiversity; economic valuation; insurance value; option value; TEV